Associations Among Self-Compassion, Eating Behaviors, and Stress in College Freshmen - Dara James; Ann Sebren; Cheryl DerAnanian; Meg Bruening; Laura Rooney; Teresa Araas; Pamela D. Swan (Journal of Basic & Applied Sciences, 2016)
Purpose: Few studies have investigated the potential relationship between self-compassion and eating behaviors. Self-compassion has been shown to improve one’s ability to respond more effectively to various situations and stressors by embracing the constructs of self-kindness, common humanity and mindfulness. This study examined correlations between self-compassion, eating behaviors and stress in first-time college freshmen. Methods: First-time freshmen (N=1477), ages 18-22 years (63% female), self-reported measures of Perceived Stress Scale (PSS), Three-Factor Eating Questionnaire (TFEQ), and Self-Compassion Scale (SCS). Associations among PSS, SCS and TFEQ scores were examined with Pearson correlations by gender. Differences by gender were explored with t-tests. Results: There were significant (p < 0.01) correlations between disinhibition and negative SCS constructs (self-judgment, r = 0.29; isolation, r = 0.23; over-identification, r = 0.28) and restraint and self-judgment in females (r = 0.26). Females scored significantly higher than males on PSS and negative SCS subscales (p < 0.05). Conclusion: Interventions increasing self-compassion and reducing stress may optimally support psychological and behavioral wellbeing as students transition into college. Future research needs to understand how self-compassion interventions may attenuate the inimical cycle of dietary restraint and disinhibition in university students.